2019
DOI: 10.3390/foods8120628
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Terpenoid Toxicity Based on a Quantitative Structure–Activity Relationship Model

Abstract: Terpenoids, including monoterpenoids (C 10 ), norisoprenoids (C 13 ), and sesquiterpenoids (C 15 ), constitute a large group of plant-derived naturally occurring secondary metabolites with highly diverse chemical structures. A quantitative structure-activity relationship (QSAR) model to predict terpenoid toxicity and to evaluate the influence of their chemical structures was developed in this study by assessing in real time the toxicity of 27 terpenoid standards using the Gram-negative bioluminescent Vibrio fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…As for the two terpenes described above, the higher nematicidal activity of E. citriodora EO can be ascribed to the functional groups present in citronellal (aldehydic function) and its derivatives compared to eucalyptol ( Figure 1 ). In specific studies aimed to evaluate the toxicity of a series of terpenes against bacterial and microbial systems [ 31 , 32 ], it was found that the presence of an oxygen-related function (as in citronellal and citronellol) and a double bond (as in citronellal) contributes to enhance the reactivity of the molecule towards biological processes involving the transfer of electrons by increasing its electronegativity.…”
Section: Discussionmentioning
confidence: 99%
“…As for the two terpenes described above, the higher nematicidal activity of E. citriodora EO can be ascribed to the functional groups present in citronellal (aldehydic function) and its derivatives compared to eucalyptol ( Figure 1 ). In specific studies aimed to evaluate the toxicity of a series of terpenes against bacterial and microbial systems [ 31 , 32 ], it was found that the presence of an oxygen-related function (as in citronellal and citronellol) and a double bond (as in citronellal) contributes to enhance the reactivity of the molecule towards biological processes involving the transfer of electrons by increasing its electronegativity.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of compositional profiles and nematicidal performances of the 16 EOs as well as of structure of their major constituents allowed some considerations on structure-activity relationships. As documented by specific studies, toxicity of natural terpenoids to nematode and bacterial and microbial systems is influenced by type and position of functional groups in their molecular structure [ 11 , 24 , 25 , 27 , 64 ]. In particular, it has been shown that biocidal activity of monoterpenoids is enhanced by the presence of an oxygen-related function (aldheyde, ketone, or alcohol group) in their molecule as well as by the presence of a double bond system which would favor biological processes involving transfer of electrons, thus increasing terpenes reactivity towards nematodes [ 27 , 64 ].…”
Section: Structure-activity Relationship: Some Considerationsmentioning
confidence: 99%
“…As documented by specific studies, toxicity of natural terpenoids to nematode and bacterial and microbial systems is influenced by type and position of functional groups in their molecular structure [ 11 , 24 , 25 , 27 , 64 ]. In particular, it has been shown that biocidal activity of monoterpenoids is enhanced by the presence of an oxygen-related function (aldheyde, ketone, or alcohol group) in their molecule as well as by the presence of a double bond system which would favor biological processes involving transfer of electrons, thus increasing terpenes reactivity towards nematodes [ 27 , 64 ]. Consistently, our in vitro assays [ 25 , 27 ] evidenced that EOs rich in citronellal, citronellol, linalool, geraniol, and E -cinnamaldehyde, such as those from C. verum , P. asperum, and E. citrodora, were highly active against M. incognita .…”
Section: Structure-activity Relationship: Some Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some terpenoids in particular are drug candidates for the treatment of human disease; examples include the sesquiterpenoid anti-malarial drug, artemisinin and diterpenoid chemotherapy drug, paclitaxel [7,8]. Most terpenoids are hydrophobic in nature and often become toxic to heterologous hosts at industrially feasible concentrations [9]. To minimize the detrimental effects of terpenoids on the host, in situ product recovery methods have become common practice at laboratory scale [10,11].…”
Section: Introductionmentioning
confidence: 99%